Carbon Dioxide Mitigation: Carbon Nano‐Onions Made Directly from CO2 by Molten Electrolysis for Greenhouse Gas Mitigation (Adv. Sustainable Syst. 10/2019). (14th October 2019) - Liu, Xinye; Ren, Jiawen; Licht, Gad; Wang, Xirui; Licht, Stuart
Abstract : In article number1900056, Stuart Licht and co‐workers, the first high yield electrosynthesis of carbon nano‐onions (CNOs) by low cost molten carbonate electrolysis is shown. The only reactant, CO2, becomes a useful, valuable resource rather than a greenhouse pollutant as a response to mitigate anthropogenic CO2 . The synthesis is achieved by excluding nucleating agents from the molten carbonate growth medium resulting in a profusion of uniform CNOs.